The Overexpression of a Transcription Factor Gene VbWRKY32 Enhances the Cold Tolerance in Verbena bonariensis - Wang, Meng-qi; Huang, Qiu-xiang; Lin, Ping; Zeng, Qin-han; Li, Yan; Liu, Qing-lin; Zhang, Lei; Pan, Yuan-zhi; Jiang, Bei-bei; Zhang, Fan (Frontiers in Plant Science, 2020)
Cold stress poses a serious threat to the survival and bloom of Verbena bonariensis. The enhancement of the cold tolerance of V. bonariensis is the central concern of our research. The WRKY transcription factor (TF) family was paid great attention to in the field of abiotic stress. The VbWRKY32 gene was obtained from V. bonariensis. The VbWRKY32 predicted protein contained two typical WRKY domains and two C2H2 zinc-finger motifs. Under cold stress, VbWRKY32 in leaves was more greatly induced than that in stems and roots. The overexpression (OE) in V. bonariensis increased cold tolerance compared with wild-type (WT). Under cold stress, the OE lines possessed showed greater recovery after cold-treatment restoration ratios, proline content, soluble sugar content, and activities of antioxidant enzymes than WT; the relative electrolyte conductivity (EL), the accumulation of malondialdehyde (MDA), hydrogen peroxide (H2O2), and superoxide anion (O2−) are lower in OE lines than that in WT. In addition, a series of cold-response genes of OE lines were compared with WT. The results revealed that VbWRKY32 worked as a positive regulator by up-regulating transcription levels of cold-responsive genes. The genes above can contribute to the elevation of antioxidant activities, maintain the membrane stability, and raise osmotic regulation ability, leading to the enhancement of the survival capacity under cold stress. According to this work, VbWRKY32 could serve as an essential gene to confer enhanced cold tolerance in plants.